Product Strategy Apple for Breaking Into the Japanese Smartphone Market - Muhammad Herdy Yudha Pratama; Andi Purnawarman (STIKes Ibnu Sina Ajibarang, 2024)
Apple's strategy to enter the Japanese smartphone market was one of its most successful historical moves. One of the critical reasons for Apple's success in Japan was its strategic cooperation with Softbank, one of the country's largest mobile service providers. Softbank was instrumental in bringing the iPhone to Japan and introducing it to Japanese consumers. This collaboration gave Apple access to Softbank's extensive distribution network and powerful promotion, significantly increasing the appeal of iPhones among smartphone users in Japan. This innovation, highlighted by the high product quality and elegant design, makes the iPhone stand out compared to its competitors. More recently, Apple has gained popularity by providing exceptional customer service. Customer loyalty has been extreme in the consumer community due to efficient customer service, consistent user experience, and a well-integrated product ecosystem (such as iCloud and antenna interoperability systems). In addition to outstanding innovation and service, Apple has positioned the iPhone at a competitive pricing point in Japan. While the iPhone is sometimes regarded as a premium product with a high price tag in many areas, Apple can offer a lower price tag in Japan than specific domestic and international competitors. This makes the iPhone more appealing to Japanese consumers, who want higher-value things.